In thumb base osteoarthritis structural damage is more strongly associated with pain than synovitis. Issue 9 (September 2018) - Kroon, F.P.B.; van Beest, S.; Ermurat, S.; Kortekaas, M.C.; Bloem, J.L.; Reijnierse, M.; Rosendaal, F.R.; Kloppenburg, M.
Summary: Objective: Osteoarthritis in thumb base joints (first carpometacarpal (CMC-1), scaphotrapeziotrapezoid (STT)) is prevalent and disabling, yet focussed studies are scarce. Our aim was to investigate associations between ultrasonographic and magnetic resonance imaging (MRI) inflammatory features, radiographic osteophytes, and thumb base pain in hand osteoarthritis patients. Design: Cross-sectional analyses were performed in cohorts with MRI ( n  = 202) and ultrasound measurements ( n  = 87). Pain upon thumb base palpation was assessed. Radiographs were scored for CMC-1/STT osteophytes. Synovial thickening, effusion and power Doppler signal in CMC-1 joints were assessed with ultrasound. MRIs were scored for synovitis and bone marrow lesions (BMLs) in CMC-1 and STT joints using OMERACT-TOMS. Associations between ultrasound/MRI features, osteophytes, and thumb base pain were assessed. Interaction between MRI features and osteophytes was explored. Results: In 289 patients (mean age 60.2, 83% women) 139/376 thumb bases were painful. Osteophyte presence was associated with pain (MRI cohort: odds ratio (OR) 5.1 (2.7–9.8)). Ultrasound features were present in 25–33% of CMC-1 joints, though no associations were seen with pain. MRI-synovitis and BMLs grade ≥2 were scored in 25% and 43% of thumb bases, and positively associated with pain (OR 3.6 (95% CI 1.7–7.6) and 3.0 (1.6–5.5)). Associations attenuated after adjustment for osteophyte presence. Combined presence of osteophytes and MRI-synovitis had an additive effect. Conclusions: Ultrasonographic and MRI inflammatory features were often present in the thumb base. Osteophytes were more strongly associated with thumb base pain than inflammatory features, in contrast to findings in finger OA studies, supporting thumb base osteoarthritis as a distinct phenotype.